The Skew Risk Premium in the Equity Index Market - Kozhan, Roman; Neuberger, Anthony; Schneider, Paul (Review of Financial Studies, 2013)
We develop a new method for measuring moment risk premiums. We find that the skew premium accounts for over 40% of the slope in the implied volatility curve in the S&P 500 market. Skew risk is tightly related to variance risk, in the sense that strategies designed to capture the one and hedge out exposure to the other earn an insignificant risk premium. This provides a new testable restriction for asset pricing models trying to capture, in particular, disaster risk premiums. We base our results on a general trading strategy by replicating contracts that swap implied for realized conditional asset moments.